Imperialism and tourism: The case of developing island countries - Sinclair-Maragh, G.; Gursoy, D (Elsevier Ltd, 2015)
The purpose of this study is to examine the perceptions residents of developing island countries have of imperialism and tourism; and consequently their support for its development. Data collected in Jamaica, a tourist-dependent and developing island country in the Caribbean were analyzed using a series of multiple regression analyses. The result shows that both the positive and negative impacts of tourism influence residents' support. Also, cultural imperialism influences residents' perceptions of the positive and negative impacts and economic imperialism influences their perceptions of the positive impacts only. One major theoretical contribution is that imperialism is examined in relation to foreign tourism investments in a developing island country.